(untitled) (Revista horizonte, 2011)
This article analyzes the degree of satisfaction of teachers who enter the teaching profession when they have finished their studies in the career of Pedagogy in Secondary Education, mentioning Physical Education, with respect to their professional training. Â We interviewed 156 graduates of both sexes (64 females 41% and 92 males 59%) enrolled between 1998-2003, belonging to the 1998 Study Plan, Internal Decree No. 1698, who have finished their studies and are working. The survey is self-administered by e-mail, where each graduate marks the category that describes his or her response to each statement. The survey presents 6 dimensions: 1) Teaching practices; 2) Infrastructure and materials; 3) Sports activities; 4) Motivation; 5) Teaching received; 6) Contents. The results obtained indicate that 59% of the graduates of both sexes affirm that they have always been interested in physical education as a profession. Males (46.2%) affirm that they are prepared to carry out their teaching practice, while females (31.4%) say they are only prepared to do so